The Hidden One: What We Know About Bitter Taste Receptor 39 - Jalševac, Florijan; Terra, Ximena; Rodríguez-Gallego, Esther; Beltran-Debón, Raúl; Blay, Maria Teresa; Pinent, Montserrat; Ardévol, Anna (Frontiers in Endocrinology, 2022)
Over thousands of years of evolution, animals have developed many ways to protect themselves. One of the most protective ways to avoid disease is to prevent the absorption of harmful components. This protective function is a basic role of bitter taste receptors (TAS2Rs), a G protein-coupled receptor family, whose presence in extraoral tissues has intrigued many researchers. In humans, there are 25 TAS2Rs, and although we know a great deal about some of them, others are still shrouded in mystery. One in this latter category is bitter taste receptor 39 (TAS2R39). Besides the oral cavity, it has also been found in the gastrointestinal tract and the respiratory, nervous and reproductive systems. TAS2R39 is a relatively non-selective receptor, which means that it can be activated by a range of mostly plant-derived compounds such as theaflavins, catechins and isoflavones. On the other hand, few antagonists for this receptor are available, since only some flavones have antagonistic properties (all of them detailed in the document). The primary role of TAS2R39 is to sense the bitter components of food and protect the organism from harmful compounds. There is also some indication that this bitter taste receptor regulates enterohormones and in turn, regulates food intake. In the respiratory system, it may be involved in the congestion process of allergic rhinitis and may stimulate inflammatory cytokines. However, more thorough research is needed to determine the precise role of TAS2R39 in these and other tissues.